2018
DOI: 10.3758/s13421-018-0873-x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive memory: Animacy, threat, and attention in free recall

Abstract: Animate items are better remembered than inanimate items, suggesting that human memory systems evolved in a way to prioritize memory for animacy. The proximate mechanisms responsible for the animacy effect are not yet known, but several possibilities have been suggested in previous research, including attention capture, mortality salience, and mental arousal (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 50 publications
2
48
1
Order By: Relevance
“…recognition, words vs. pictures, different encoding instructions) (Bonin et al, 2014(Bonin et al, , 2015Gelin et al, 2017). Later work has further built on this foundation to first suggest potential mechanisms (e.g., Bonin et al, 2015;Popp & Serra, 2016), though many of these have since been ruled out, such as being mediated by imagery (Gelin et al, 2019), emotional arousal (Popp & Serra, 2018;Meinhardt et al, 2018), or threat (Leding, 2019). Some studies have suggested that the memory enhancement due to animacy may relate to an attentional capture mechanism (e.g., Popp & Serra, 2016;Gelin et al, 2017;Bugaiska et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…recognition, words vs. pictures, different encoding instructions) (Bonin et al, 2014(Bonin et al, , 2015Gelin et al, 2017). Later work has further built on this foundation to first suggest potential mechanisms (e.g., Bonin et al, 2015;Popp & Serra, 2016), though many of these have since been ruled out, such as being mediated by imagery (Gelin et al, 2019), emotional arousal (Popp & Serra, 2018;Meinhardt et al, 2018), or threat (Leding, 2019). Some studies have suggested that the memory enhancement due to animacy may relate to an attentional capture mechanism (e.g., Popp & Serra, 2016;Gelin et al, 2017;Bugaiska et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Some properties are related to their lexical features, such as the number of letters (better recall for short words; e.g., Frincke, 1968;Baddeley et al, 1975;Hulme et al, 2004;Tehan & Tolan, 2007), number of syllables (better recall for fewer syllables; e.g., Watkins, 1972;Baddeley et al, 1975;Hulme et al, 2004), word frequency (better recall for high frequency; e.g., Hall, 1954;Sumby, 1963;Gregg, 1976;Madan et al, 2010;Popov & Reder, 2019), and orthographic neighbourhood size (better recall for more neighbours; e.g., Jalbert et al, 2011aJalbert et al, , 2011bGlanc & Greene, 2012). Other properties are related to their semantic features, such as age of acquisition (better recall for late acquired; e.g., Morris, 1981;Dewhurst et al, 1998), concreteness (better recall for high concreteness; e.g., Stoke, 1929;Paivio et al, 1968;Frincke, 1968;Madan et al, 2010), animacy (better recall for living things [discussed in more detail in the Methods section]; e.g., Nairne et al, 2013;Bonin et al, 2014Bonin et al, , 2015Popp & Serra, 2016;Gelin et al, 2017;Leding, 2019), number of features/semantic richness (better recall for higher number of features; e.g., Hargreaves et al, 2012), and motoric properties (better recall for words referring to functional objects; Madan & Singhal, 2012;Montefinese et al, 2013;Madan, 2014). Additionally, affective properties such as arousal and valence are also related to recall (better recall for high arousal and more extreme valence; e.g., Kensinger & Corkin, 2003;Buch...…”
mentioning
confidence: 99%
“…Because threatening items are more likely to capture attention and because animate stimuli often include items that would be perceived as threatening, the independent manipulation of animacy and threat was recently explored in the animacy effect. A norming study was conducted to create a list of animate and inanimate objects that were classified as either threatening or non-threatening (Leding, 2019a). In several experiments testing recall memory, the animacy effect persisted across both threatening and non-threatening items, suggesting the animacy effect in memory does not rely on the perceived threat of animate items (Leding, 2019a(Leding, , 2019b.…”
Section: Animacy and Threatmentioning
confidence: 99%
“…A norming study was conducted to create a list of animate and inanimate objects that were classified as either threatening or non-threatening (Leding, 2019a). In several experiments testing recall memory, the animacy effect persisted across both threatening and non-threatening items, suggesting the animacy effect in memory does not rely on the perceived threat of animate items (Leding, 2019a(Leding, , 2019b. There was also an effect of threat such that threatening items were recalled more often than non-threatening items.…”
Section: Animacy and Threatmentioning
confidence: 99%
See 1 more Smart Citation